Assessing the pedestrian network conditions in two cities: the cases of Qazvin and Porto - Jabbari, Mona (2020)
The quality of life in cities depends on the existence of suitable conditions to walk. The aim of this chapter is to assess the conditions provided to pedestrians in two cities with different urban morphologies: Qazvin (Iran) and Porto (Portugal). The assessment was performed through a model that combines multi-criteria analysis with street network connectivity to evaluate the pedestrian conditions. The multi-criteria analysis was carried out by using four criteria and nine sub-criteria that mostly influence walkability and by involving a group of experts from Qazvin and Porto. Street network connectivity was assessed by Space Syntax. Results showed that Qazvin provides better conditions and a network of pedestrian streets more connected than Porto. The model can be a useful tool for planning more walkable and sustainable cities in urban areas.